Health Insurance Expansions and Provider Behavior: Evidence from Substance Use Disorder Providers - J. Catherine Maclean; Ioana Popovici; Elisheva Rachel Stern (Institute of Labor Economics (IZA), 2017)
We examine how substance use disorder (SUD) treatment providers respond to private health insurance expansions induced by state equal coverage ('parity') laws for SUD treatment. We use data on the near universe of specialty SUD treatment providers in the United States between 1997 and 2010 in an event study analysis. During this period, 18 states implemented parity laws. Following the passage of a state parity law we find that providers are less likely to participate in public markets, are less likely to provide charity care, increase the quantity of healthcare provided, and become more selective of the type of patients they are willing to admit.
Keywords: I1; I11; I18; 330; healthcare; provider behavior; substance use disorders; health insurance mandates